Perioperative outcomes in intermediate and high-risk patients after major surgery following introduction of a dedicated perioperative medicine team: A single centre cohort study. Issue 2 (March 2023) - Nicholson, Jonathan J; Reilly, Jennifer; Shulman, Mark A; Ferguson, Marissa; Burke, Justin A; Lehane, Daragh N; Liaw, Chen-Mei; Mahoney, Adam; Stark, Peter; Myles, Paul S
Intermediate and high-risk patients undergoing surgery are often managed on a surgical ward in the absence of haemodynamic or ventilatory support requirements necessitating intensive care unit or high dependency unit admission. We describe a model of care for the multidisciplinary management of selected postoperative patients and the epidemiology of patients managed using this model at a tertiary Australian hospital. Of 25, 139 patients undergoing inpatient surgery at our institution over a two-year period, 506 (2%) were referred to the Perioperative Medicine team. The median age of patients referred was 74 years; 85% had an American Society of Anesthesiologists physical status ≥3, and 44% underwent emergency surgery. Major complication or death within 30 days was 44.2% (213/482). The most common complications, as defined by the American College of Surgeons National Surgical Quality Improvement Program were transfusion within 72 h (17.4%), pneumonia/aspiration pneumonitis (11.3%), and acute renal failure (10.6%); median time to Medical Emergency Team call was 146 (interquartile range 77–279) h. Sixty-six percent of referred patients (280/423) required an intervention during their time under the service. This high incidence indicates that this population of patients merits closer attention, including routine measurement and reporting of postoperative outcomes to monitor and improve quality of care at our institution as part of an integrated perioperative service. We believe that with so much current focus on perioperative medicine, it is important we translate this to clinical care by evolving traditional models of management into more innovative strategies to meet the complex demands of today's surgical patients.